Censorship detected in RU (Russia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Russia. Data sourced from OONI.
Censorship Incident ID: RU-2026-2970. Severity: critical. Confidence: 89%